Decreased methionine synthesis in purine nucleoside-treated T and B lymphoblasts and reversal by homocysteine. - Boss, G R (1984)
Purine nucleosides, which accumulate in adenosine deaminase and purine nucleoside phosphorylase deficiency, are toxic to lymphoid cells. Since adenine nucleosides inhibit S-adenosylhomocysteine hydrolase, they could potentially decrease intracellular methionine synthesis. To test this hypothesis, we measured methionine synthesis by the use of [14C]formate as a radioactive precursor in cultured human T and B lymphoblasts treated with varying concentrations of purine nucleosides; 2'-deoxycoformycin and 8-aminoguanosine were added to inhibit adenosine deaminase and purine nucleoside phosphorylase, respectively. In the T lymphoblasts methionine synthesis was inhibited approximately 50% by 10 microM of 2'-deoxyadenosine, adenine arabinoside, or 2'-deoxyguanosine. By contrast, in the B lymphoblasts methionine synthesis was considerably less affected by these nucleosides, with 50% inhibition occurring at 100 microM of 2'-deoxyadenosine and adenine arabinoside; 100 microM of 2'-deoxyguanosine yielded less than 10% inhibition. Adenosine and guanosine were considerably less potent inhibitors of methionine synthesis in both the T and B lymphoblasts. An adenosine deaminase-deficient and a purine nucleoside phosphorylase-deficient cell line, both of B cell origin, exhibited sensitivities to the nucleosides similar to those of the normal B cell lines. In both the T and B cell lines homocysteine reversed the methionine synthesis inhibition induced by the adenine nucleosides and guanosine and largely reversed that induced by 2'-deoxyguanosine. Methionine synthesis from homocysteine generates free tetrahydrofolate from 5-methyltetrahydrofolate, the main intracellular storage form of folate. We conclude that purine nucleoside toxicity may be partly mediated through (a) decreased intracellular methionine synthesis, and (b) altered folate metabolism.